(Un)reading orientalism in Sherry Jones’ The Jewel of Medina - Abubakar, Sadiya; Md. Salleh Yaapar,; Suzana Muhammad, (Penerbit Universiti Kebangsaan Malaysia, 2019)
Oriental representations of Muslims are often manifested in a society's media, literature, theatre and other creative means of expression. However, these representations, which are often historically and conceptually one-sided, have adverse repercussions for Muslims today, potentially leading to Islamophobia. Orientalism of Muslims in Western writings and discourses have been much discussed, debated and disproved, yet some works of literature continue to disseminate many of the earlier Oriental assertions about Islam/Muslims: that of being terrorists, misogynists, barbaric or uncivilized compared to the civilized West. Sherry Jones’ The Jewel of Medina (2008) chronicles the history of Islam from the time of the Prophet of Islam, Muhammad, through the voice of his youngest wife Aisha. This paper argues that there is more to the image of the Muslim than what is portrayed by Western writers. Through an “(un)reading” of Sherry Jones’ text, this paper unravels the misconceptions regarding early and forced marriage with a view to address the ways in which these misconceptions could lead to Islamophobia. Using Edward Said's theory of Contrapuntal reading, which urges the colonized to unread Western canonical texts to unearth the submerged details, this paper identifies and puts to question non-conforming depictions of Muslims in Sherry Jones’ The Jewel of Medina (2008) – while placing the text in its historical space – in an effort to mitigate the growing stereotyping of Muslims and to address misconceptions with regard to Islamic history.